ASSESSING THE ROLE OF FINTECH IN FINANCIAL INCLUSION IN EMERGING MARKETS - Sharma, Pradeep; Gupta, Monica (ShodhKosh: Journal of Visual and Performing Arts, 2023)
FinTech has emerged as a powerful mediator for enhancing financial inclusion across emerging markets of the world and is also addressing persistent barriers to access traditional banking services, poor financial literacy, high transaction costs, and lack of trust in financial institutions. This study presents a paradigm for evaluating the effect of FinTech in improving financial inclusion in emerging markets, taking into account the fundamental variables that influence FinTech adoption. The paradigm also takes into account the mediating role of financial literacy in the digital age, as well as the moderating influence of perceived regulatory support on the link among finance technology adoption and financial inclusion. Literature identified in the proposed framework by simultaneously assessing the relationships between key factors like trust, service quality, perceived security, FinTech adoption, digital financial literacy, perceived regulatory support, and financial inclusion, while evaluating both direct and indirect effects to test the research hypotheses. According to the hypothesis, digital financial literacy is intended to play an intermediary role in the link between adoption of finance technology and financial inclusion, tempered by perceived regulatory support. The findings should have significant importance in providing insights into the factors that foster FinTech adoption and their role in driving financial inclusion, together with a number of practical recommendations on how to enhance digital financial literacy and regulatory environments to support FinTech innovations in emerging markets.